Designers guide to Eurocode 5 design of timber buildings : EN 1995-1-1 - Porteous, Jack (Eurocode designers' guide series, 2012)
This guide interprets and assists in the use of EN 1995-1-1 structural timber. Showing typical material properties and dimensions; modifiers, and structural reponses, it presents concise worked examples. Connections, an especially critical aspect of timber design, are thoroughly addressed. Relationships with other Eurocodes are explained, particularly those for EN 1990 Basis of Design. It cites British Standard - European Standard (BS EN) documents supporting the Construction Products Directive in structural timberwork. Copious references permit readers to investigate beyond the code background within the guide itself.